Bacterial Proteases as Thrombolytics and Fibrinolytics - Akhtar, Taqiyah; Hoq, Md Mozammel; Mazid, Md Abdul (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Proteases regulate important pathophysiological processes in human body such as homeostasis, blood coagulation, fibrinolysis, tumor progression, etc. These biological effects of proteases largely attribute to their applicability as therapeutic agents. Imbalance in blood coagulation and fibrinolysis, two important physiological processes in human body, leads to thrombosis, a leading cause of cardiovascular complications including myocardial infarction, stroke, etc. The enzymes used to dissolve thrombus (blood clot) are known as thrombolytic agents and among them, the enzymes involving hydrolysis of fibrin called fibrinolytic agents. Thrombolytic agents can be classified according to generation, mechanism of action, source and active site of the enzymes. Among the commercially available thrombolytic agents, uPA and tPA are generally safe but are very expensive. On the other hand, the bacterial streptokinase is a relatively cheap thrombolytic agent but causes undesirable side effects such as bleeding complications. For this reason, worldwide research for potent thrombolytic agents to prevent and treat cardiovascular diseases have been continuing. Microbes are considered as a potential source of as well as safe vectors for expressing thrombolytic and fibrinolytic enzymes. Bacilli are one of the largest groups for this purpose. They have been collected from different traditional fermented foods or have been produced by solid state fermentation using appropriate nutrient substrates including different agro-industrial wastes such as rice straw, molasses, soybean curd residues, etc. This review focuses on different bacterial proteases reported to have potential thrombolytic and fibrinolytic activities. Dhaka Univ. J. Pharm. Sci. 16(2): 255-269, 2017 (December)